2013
DOI: 10.1021/ic302798u
|View full text |Cite
|
Sign up to set email alerts
|

Integrated and Passive 1,2,3-Triazolyl Groups in Fluorescent Indicators for Zinc(II) Ions: Thermodynamic and Kinetic Evaluations

Abstract: In addition to being a covalent linker in molecular conjugation chemistry, the function of a 1,2,3-triazolyl moiety resulting from the copper(I)-catalyzed azide-alkyne cycloaddition reaction as a ligand for metal ions is receiving considerable attention. In this work, we characterize the thermodynamic and kinetic effects of incorporating a 1,2,3-triazolyl group in a multidentate ligand scaffold on metal coordination in the context of fluorescent zinc(II) indicator development. Ligands L14, BrL14, and FL14 (1,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 88 publications
(155 reference statements)
3
49
0
Order By: Relevance
“…Studies to determine the binding model by using the method of continuous variations (Job's plot, see Figure S9) suggest a 2:1 stoichiometry for the Cd 2+ complex with the ligand. We suggest a possible way in which the Cd 2+ ions interact with the binding sites in 6 on the basis of previous reports [2][3][4][5][6] (Figure 5). Figure 6 shows that in the presence of Cd 2+ ions the absorption band of probe 6 does not undergo displacement, but a hypochromic effect (fluorescence quenching as a result of photoinduced electron transfer) is observed that is possibly related to interactions between the probe and the…”
Section: Selectivity and Titration Of CD 2+ Withsupporting
confidence: 67%
See 1 more Smart Citation
“…Studies to determine the binding model by using the method of continuous variations (Job's plot, see Figure S9) suggest a 2:1 stoichiometry for the Cd 2+ complex with the ligand. We suggest a possible way in which the Cd 2+ ions interact with the binding sites in 6 on the basis of previous reports [2][3][4][5][6] (Figure 5). Figure 6 shows that in the presence of Cd 2+ ions the absorption band of probe 6 does not undergo displacement, but a hypochromic effect (fluorescence quenching as a result of photoinduced electron transfer) is observed that is possibly related to interactions between the probe and the…”
Section: Selectivity and Titration Of CD 2+ Withsupporting
confidence: 67%
“…[1] Zhu and co-workers described coumarins linked with this ligand obtained by copper-catalyzed azide-alkyne cycloaddition (CuAAC) and the versatility of the obtained compound as a zinc-selective fluorescent sensor. [2] A similar approach was used by Rosenthal and Lippard to prepare a boron-dipyrromethene (BODIPY)-based ligand designed as a nitric oxide sensor. [3] Torroba and co-workers developed a colorimetric and fluorescent probe to detect Cu II ions selectively.…”
Section: Introductionmentioning
confidence: 99%
“…The solution structure of [Zn(1) 2 ](ClO 4 ) 2 replicates that in the solid state (13). The two 2-pyridylmethyl groups on one DPA ligand are no longer in the same chemical environment.…”
Section: Introductionmentioning
confidence: 64%
“…The downfield shifts are expected because the positively charged zinc(II) ion deshields the protons via the inductive effect. The methylene protons H(x) next to the 2-pyridyl are now non-equivalent, as they are part of the kinetically stable five-membered coordination rings (13). Therefore, two doublets for two H(x) 0 s are observed.…”
Section: H Nmr (600 Mhz CD 3 Cn) Studiesmentioning
confidence: 99%
“…The investigation on fluorescent sensing of metal ions is promising because heavy metals play crucial roles in ecological, biological, and clinical applications [1][2][3][4][5]. In biological systems, zinc(II) is the second most abundant transition metal only next to iron [6,7].…”
Section: Introductionmentioning
confidence: 99%